Chen, C.J. (2010). Virtual reality (VR)-based learning environment: Design, develop, evaluate. - Chen, Chwen Jen (LAP LAMBERT Academic Publishing, 2010)
This book proposes an instructional design theoretical framework that prescribes instructional and design methods for virtual reality (VR)-based learning environments. It provides a thorough description on how to use a constructivist instructional development model to guide the process of designing, developing and evaluating VR-based learning environments. A learning environment that focuses on the understanding of traffic rules for various road scenarios is used to illustrate the feasibility of the instructional design theoretical framework and the instructional development model. An evaluation that employs a quasi-experimental design is then conducted to investigate effects of the developed learning environment, effects of controlling the exploration through virtual environments; and effects of learners? aptitudes, both spatial visualisation ability and learning style, on learning. This book will be of interest to instructional designers, instructional technologists, learning scientists and educators who seek a better understanding of producing effective VR-based learning environments.